THE CABO DELGADO INSURGENCY AND MOZAMBIQUE’S OBLIGATION TO PROVIDE FOREIGN INVESTORS WITH FULL PROTECTION AND SECURITY - Koen, Louis (Obiter, 2022)
Mozambique is currently facing a violent and rapidly escalating insurgency within its Cabo Delgado province. The province is rich in mineral resources and has attracted substantial foreign investment. In terms of most of its bilateral investment treaties, Mozambique has agreed to provide foreign investors with full protection and security (FPS) within its territory. This article explores the extent of a state’s obligations to foreign investors under the FPS standard in international investment law. It finds that tribunals have adopted diverging interpretations of the standard and critiques several of these approaches. In particular, it expresses concern over the extent to which investment law forces the state to choose between protecting its people and protecting investors’ assets. It also reflects on what these diverging interpretations mean for Mozambique and the extent to which it may be liable to compensate investors for harm caused to their property by the insurgents. It is argued that investment tribunals should be alive to the various demands on state resources and not simply base liability on the foreseeability of harm. It also concludes by suggesting that Mozambique should seek an agreement with its treaty partners to temporarily restrict the extent of its liability under the FPS standard.